Optimization of sensorless sliding mode control of an induction motor taking into account magnetic saturation effects - KENMOE FANKEM, Eric Duckler; Fatamou, Hiswe; Dountio Tchioffo, Alix; Dountio Tchioffo, Alix; Effa, Joseph Yves (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This paper presents the optimization of sensorless sliding-mode control for induction motor, considering magnetic saturation effects. A five-order sliding-mode observers and estimators are elaborated to replace the sensors of an induction motor. The proposal is based on double optimization of sensorless sliding mode control of an induction motor in the point of view of dynamic and energetic performances. In order to obtain better performances of the proposed control method, Particle Swarm Optimization (PSO) algorithm is used notably to determine the optimal gains of the observers as well as the optimal parameters of the regulators. Regarding the energetic optimization, the reference of the rotor flux is generated using another developed algorithm that permits us to dynamically determine the optimal rotor flux for each given value of motor load and speed. As results, sensorless sliding mode control takes into account all operating ranges of the machine from very low speeds, low speeds, to high speed with or without load. Numerical simulations are carried out each time to confirm theoretical predictions.